Effect of feed barrier design and feed space allowance on performance and behavioural parameters in dairy cows - O’Connell, Niamh E.; Ferris, Conrad P.; Patterson, Desmond C.; Mayne, C. Sinclair (Applied animal behaviour science, 2010)
Sixty mid-lactation Holstein–Friesian dairy cows (40 multiparous (cows) and 20 primiparous (heifers)) were allocated to one of four treatments in a 2 × 2 factorial design arrangement. The treatments involved two feed barrier space allowances (56 cm/animal (“high”) or 20 cm/animal (“low”)) and two feed barrier designs (‘open’ or ‘individual headspaces’). The ‘open’ barrier was a standard post and rail design, whereas ‘individual headspaces’ were created using vertical bars. Cows were housed in groups of 15 animals (10 cows and 5 heifers). A completely balanced changeover design was applied over four 5-week periods. Behavioural parameters were recorded during weeks 4 and 5 of each experimental period, while cow performance was recorded during Week 5. Behavioural scans were taken at 30 min intervals during two non-consecutive 24-h periods in each recording week. The total number of animals, and the proportion of these animals that were heifers, at the feed barrier and in the passageway behind the feed barrier were recorded. In addition, aggressive behaviour was recorded for 1 h after morning and evening milking on 1 day during each recording week. Due to technical difficulties, aggressive behaviour was not recorded in the ‘open barrier/high space allowance’ treatment. There was no significant effect of treatment on production performance parameters including dry matter intake (DMI) and average daily milk yield (average values: 21.7 and 32.0 kg/day, respectively). The average number of animals at the feed barrier increased as feed barrier space allowance increased (‘high’ 3.8, ‘low’ 2.8, SEM 0.08, F 1,9 78.3, P < 0.001), but was not significantly affected by barrier design. The proportion of animals at the feed barrier or in the feed passage that were heifers, and the total number of animals in the feed passage, was not significantly affected by treatment (average values: 0.34, 0.31, 0.55 animals, respectively). The total level of aggression was significantly higher in the ‘individual headspaces/low feed space allowance’ treatment than in the other two treatments (‘individual headspaces/low’ 1.07, ‘open/low’ 0.41, ‘individual headspaces/high’ 0.29, SEM 0.170 (interac./animal/10 min), F 2,15 12.04, P ≤ 0.001). It is suggested that it is more difficult to displace animals when individual headspaces are used, and that this exacerbates aggression in competitive situations. It is concluded that reducing feed barrier space allowance from 56 to 20 cm/animal does not adversely affect feed intake or milk yield levels in mid-lactation dairy cows when using either open barrier or individual headspace barriers. In addition, using individual feed spaces at low feed barrier space allocations appears to exacerbate aggression, which may have negative welfare implications.